Economic efficiency analysis of vegetable production systems during 2011 - 2014 - Ana Ursu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Economic efficiency plays an important role in the foundation and farm level decisions, constituting a basic criterion in assessing the level of economic activity and development prospects. The study aimed to analyze the economic efficiency of crop production systems, measured through indicators that contribute to an overall picture of the actual conditions of economic efficiency for the analyzed period. For this study were quantified following indicators: income from operations, operating costs, labor productivity and rate of return on different types of farms of different sizes. The analysis concluded that indicators production year 2013-2014 has showed a lower level of economic efficiency compared with 2011-2012 production year; comparison of the two production systems that irrigated production system provides a rate of return of about 9-10% higher than non-irrigated system. Comparing labor productivity in terms of value (lei / Man-hour) the types of farms of different sizes that hourly labor productivity increases with economic size of holding and decreases as the number of man-hours to 1000 lei incomes increase.
Keywords: 330; economic efficiency; production systems; labor productivity; profitability